The labor market effects of immigration and emigration in OECD countries - Frédéric Docquier; Caglar Ozden; Giovanni Peri (Institute for the Study of Labor (IZA), 2011)
In this paper, we simulate the labor market effects of net immigration and emigration during the 1990's in all OECD countries. To accomplish this, we are the first to employ a comprehensive database of migrant stocks, grouped by education level and country of origin/destination, for the years 1990 and 2000. Due to the much higher international mobility of college graduates, relative to all other individuals, we find that net migration flows are college-intensive, relative to the population of non-migrants. Using the consensus aggregate model of labor demand and supply we simulate the long-run employment and wage effects of immigration and emigration. We use a range of parameter values spanning most of the estimates in the literature. In all cases we find that immigration had a positive effect on the wage of less educated natives. It also increased or left the average native wages unchanged and had a positive or no effect on native employment. To the contrary, emigration had a negative effect on the wage of less educated native workers and it contributed to increase within country inequality in all OECD countries. These results still hold true when we correct for the estimates of undocumented immigrants, for the skill-downgrading of immigrants, when we focus on immigration from non-OECD countries, and when we consider preliminary measures of more recent immigration flows for the period 2000-2007.
urn:nbn:de:101:1-201203016386
Keywords: F22; J61; J31; 330; immigration and emigration; complementarity; schooling externalities; average wage; wage inequality; Internationale Wanderung; Einwanderung; Auswanderung; Qualifikation; Lohnstruktur; Beschäftigungseffekt; OECD-Staaten